Measuring professional satisfaction in Greek nurses: combination of qualitative and quantitative investigation to evaluate the validity and reliability of the index of work satisfaction - Papathanassoglou, Elizabeth; Karanikola, Maria (My University, 2015)
Purpose The Index of Work Satisfaction (IWS) is a comprehensive scale assessing nurses' professional satisfaction. The aim of the present study was to explore: a) the applicability, reliability and validity of the Greek version of the IWS and b) contrasts among the factors addressed by IWS against the main themes emerging from a qualitative phenomenological investigation of nurses' professional experiences. Methods A descriptive correlational design was applied using a sample of 246 emergency and critical care nurses. Internal consistency and test–retest reliability were tested. Construct and content validity were assessed by factor analysis, and through qualitative phenomenological analysis with a purposive sample of 12 nurses. Scale factors were contrasted to qualitative themes to assure that IWS embraces all aspects of Greek nurses' professional satisfaction. Results The internal consistency (α = 0.81) and test–retest (tau = 1, p < 0.0001) reliability were adequate. Following appropriate modifications, factor analysis confirmed the construct validity of the scale and subscales. The qualitative data partially clarified the low reliability of one subscale. Conclusions The Greek version of the IWS scale is supported for use in acute care. The mixed methods approach constitutes a powerful tool for transferring scales to different cultures and healthcare systems.
Keywords: Critical care; Emergency; Greece; Job satisfaction; Phenomenology; Professional status